Surface wave characteristics in a micropolar transversely isotropic halfspace underlying an inviscid liquid layer - Gupta, Rajani Rani; Gupta, Raj Rani (Zielona Góra: Uniwersytet Zielonogórski)
The present investigation deals with the propagation of waves in a micropolar transversely isotropic half space with an overlying inviscid fluid layer. Effects of fluid loading and anisotropy on the phase velocity, attenuation coefficient, specific loss and relative frequency shift. Finally, a numerical solution was carried out for aluminium epoxy material and the computer simulated results for the phase velocity, attenuation coefficient, specific loss and relative frequency shift are presented graphically.
Keywords: micropolar; transversely isotropic; amplitude ratios; Rayleigh waves